2016
DOI: 10.3389/fncir.2016.00033
|View full text |Cite
|
Sign up to set email alerts
|

Chandelier Cells in Functional and Dysfunctional Neural Circuits

Abstract: Chandelier cells (ChCs; also called axo-axonic cells) are a specialized GABAergic interneuron subtype that selectively innervates pyramidal neurons at the axon initial segment (AIS), the site of action potential generation. ChC connectivity allows for powerful yet precise modulation of large populations of pyramidal cells, suggesting ChCs have a critical role in brain functions. Dysfunctions in ChC connectivity are associated with brain disorders such as epilepsy and schizophrenia; however, whether this is cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 121 publications
0
35
0
Order By: Relevance
“…A role for AIS abnormalities in epilepsy has been suggested in other studies 55 57 , implicating trafficking and localization of voltage-gated channels to the AIS. Other analyses have found alterations to AIS inhibitory synapses resulting from or contributing to epilepsy; however, both decreases and increases in AIS synapse number have been found, leaving the contribution of this synaptic subtype unclear 58 60 . Our results directly link a mutation in a specific GABA A R-subunit, accompanied by an alteration in AIS GABAergic synapses, to an epileptic phenotype.…”
Section: Discussionmentioning
confidence: 95%
“…A role for AIS abnormalities in epilepsy has been suggested in other studies 55 57 , implicating trafficking and localization of voltage-gated channels to the AIS. Other analyses have found alterations to AIS inhibitory synapses resulting from or contributing to epilepsy; however, both decreases and increases in AIS synapse number have been found, leaving the contribution of this synaptic subtype unclear 58 60 . Our results directly link a mutation in a specific GABA A R-subunit, accompanied by an alteration in AIS GABAergic synapses, to an epileptic phenotype.…”
Section: Discussionmentioning
confidence: 95%
“…These cells form vertically oriented clusters of axon terminals, called cartridges, giving them a chandelier-like appearance. A single pyramidal cell receives contacts from multiple chandelier cells 97 , forming an average of 3 to 5 boutons each 98 depending on the brain region 99 and age 100 . The synapses are enriched for the GABAAα2 receptor subunit 101 , 102 and pre-synaptically express the high-affinity GABA transporter 1 (GAT1) 103 .…”
Section: The Central Role Of Parvalbumin-positive Interneurons In E/imentioning
confidence: 99%
“…Since their discovery, there has been a debate about the actions of chandelier cells (reviewed by Wang and colleagues 98 ). Some studies using brain slice recordings showed a depolarizing 108 and even excitatory 109 action for these interneurons, whereas others report an inhibitory action 110 .…”
Section: The Central Role Of Parvalbumin-positive Interneurons In E/imentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, excitatory PVChCs would support the hypothesis of insufficient excitation between pyramidal cells, with a homeostatic reduction of PVBC inhibition and an increase in excitation by PVChCs as compensatory mechanisms. The question of whether PVChCs have excitatory effects on principal cells in adult in vivo brain is not yet settled …”
Section: The Gabaergic System and Excitation/inhibition Disbalance Inmentioning
confidence: 99%